Altered strategy in the treatment of patients with recurrent ovarian cancer. According to the proceedings of the 5th International Conference on Gynecologic Oncology hosted by the MD Anderson Cancer Center (Madrid, Spain, 24-26 February 2016) - A. G. Kedrova (ABV-press, 2016)
The paper highlights main areas in the development of European oncology care to patients with malignant ovarian neoplasms. It discusses the major issues considered at the 5th Annual Meeting of Oncologists on Arrangement of Anticancer Therapy into the Era of Personalized Therapy hosted by the MD Anderson Cancer Center.